Surat Berharga sebagai Bentuk Penyetoran Modal dalam Pendirian Perseroan Terbatas - Sonya Whisler Refisyanti; Mohamad Fajri Mekka Putra (Faculty of Law, University of Mataram, 2023)
There are various types of business entities in Indonesia, namely divided into non-legal entities and legal entities. One of which frequently chosen by the business actor is a limited liability company (PT) due to its limited liability which only need to provide a capital that has separate assets between private ownership and the company. To establish a Limited Liability Company, the Company will need a Capital Deposit to run the business. Usually, the capital is paid in cash. The research aims to determine whether the capital deposit required to establish a limited liability company can be paid using a method other than Cash. The research is using a normative legal research by using statute and library approach. The research findings reveal that according to Article 34 paragraph (1), the capital deposit can be made in Cash and/or other forms. It means if the Capital Deposit, which is paid in other forms, can be valued in money, and accepted, as well as approved, by the Company’s founders. Payment of shares in securities must be announced, at least, in 1 (one) newspaper or more within 14 (fourteen) days after the deed of establishment is signed or after the General Meeting of Shareholders decides on the payment of shares.